BUILDING ON SUCCESS: REVISITING THE TELE-ARAL PROGRAM THROUGH THE LENS OF APPRECIATIVE INQUIRY: Received: 23rd March 2023; Revised: 12th August 2023, 23rd August 2023; Accepted: 25th August 2023 - Honra, Joelash (PUPIL: International Journal of Teaching, Education and Learning, 2023)
As the pandemic challenges the education sector, alternative and innovative delivery of quality education has to be done. Notably, this study focused on a qualitative investigation of the successes and strengths of the Tele-Aral program using the 4-D process of Appreciative Inquiry (AI). The data were gathered using both semi-structured interviews and focus group discussions. Guides for the interviews and FGDs were aligned with the research questions and validated by experts. Similarly, I followed the ethical research standards to protect human subjects while maintaining the study’s trustworthiness. Additionally, nonprobability sampling techniques such as purposeful and criterion sampling were used in determining the study participants. Then, the data were thematically analyzed and methodologically triangulated. The findings revealed that the Tele-Aral program gave specific benefits to its stakeholders during the discovery stage. Participants envisioned that the program would become more successful in catering to struggling learners in the future. To achieve and sustain these visions, the participants looked into personal and collective upskilling and promoting the program to the local government units to reach more learners. Furthermore, I recommend that education stakeholders explore using appreciative inquiry in making various school reforms. Likewise, further studies are encouraged, focusing on the limitations of this study.